Real job market in the metropolitan area of San Salvador for professionals graduated in Licenciatura en Idioma Inglés opción Enseñanza, main campus, of the University of El Salvador - Gamero Flores, Ruth Elizabeth; Pérez Rodezno de Aguilar, Irma Dinora; Ayala, Edgar Nicolás; Salazar Murcia, Pedro Antonio (San Salvador : Universidad de El Salvador, 2007)
People coming to the university expect to have a better life: a house for the present or future family, a good job, food, clothing and maybe a car. Some travel from far away cities like Cojutepeque or the like and endeavor in a long effort to finish a major. Some see in English the way to make their dreams come true. They believe English will open doors to a land pouring milk and honey. Youths see themselves traveling around the world on a plane, working for an international company, and making business with foreigners who speak no Spanish at all. Of course, there are those who expect to be school or university teachers, dedicating a whole life to help others learn new things, discover a world of knowledge and guide them to a fruitful and useful tomorrow, even serving as models to future generations. Unfortunately, some realize there is no gold pot at the end of the rainbow. At the beginning of their English major, they expect to work for airlines, large hotels as administrators, and even in embassies or prestigious banks. To their surprise, it is not quite easy to do so, if not impossible in some cases. This is the case of working for embassies and banks. As a result, there are those who end up doing something they never wanted at the start: as teachers, getting bitter and making others bitter; in hotels getting poor wages, or as secretaries, losing their English and thinking of their university studies as a past event which left them but a diploma hung on a wall at home. Others realize too late that getting a job at an embassy is for the ones who have really good connections and can get high level recommendations. Banks, on the other hand, seem not to hire anybody on the base of only knowing English. It is much cheaper and practical for them to send their qualified personnel to an English academy than teaching an English speaker specialized knowledge on finances and the like. At the beginning of the English major, some students seem to have wrong expectations which lead them to wrong results.
Tesis (Licenciatura en Idioma Inglés opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2007
Keywords: Inglés -- Enseñanza; Lingüístas -- Mercado laboral -- El Salvador